Impacts of Kaolin and Pinoline foliar application on growth, yield and water use efficiency of tomato (Solanum lycopersicum L.) grown under water deficit: A comparative study - Ahmed AbdAllah (Journal of the Saudi Society of Agricultural Sciences)
The impacts of Kaolin particle film (KPF) and Pinoline (P) Antitranspirants (ATs) on growth, yield components (marketable and unmarketable), fruit quality and on-farm irrigation water use efficiency (WUE) of tomato plants (Solanum lycopersicum L.) grown under water deficit of 40%, 60%, and 80% depletion of available water (DAW) were studied, to determine if ATs application would mitigate water deficit stress and increase WUE. The field experiments were elaborated in the open field for two seasons under the drip irrigation system. The results revealed that deficit irrigation (DI) significantly reduced the relative water content of the leaves (RWC), CO2 assimilation rate (P-net), marketable yield, while canopy temperature (CT) and WUE were increased. Results indicated that KPF under DI effectively enhanced the physiological activities and marketable yield production, while reduced sunscald fruits and those with blossom-end rot symptoms (unmarketable yield), particularly under 60%DWA, but it did not compensate the negative effects under 80%DWA. Also, the effect was null under non-limiting water conditions. Generally, P had no significant effects under different water stress severities. Under 60%DWA, application of KPF increased the marketable yield to 93% of the unstressed-unsprayed plants, while conserving 25% of irrigation water, leading to an increase in WUE by 26.24% with respect to unstressed-unsprayed plants. Keywords: Antitranspirants, Water use efficiency, Kaolin, Pinoline, Transpiration rate, Deficit irrigation